En prædikescene i sten - Bolander, Lisbet (Hikuin, 2017)
A preaching scene in stone Lisbet Bolander A very rare motif in the Western European stone sculpture can be seen at two baptismal fonts, attributed to the anonymous master Calcarius from Gotland, Sweden. The workshop is dated to the second quarter of 1200-century. Respectively on the bottom of the bowl (Skelby, Denmark) and on the shaft (Fole, Gotland) is played out a bizarre scene with a wolf dressed like a monk who is preaching for a ram. The Bible warns against false prophets (”wolf in sheep’s clothing”) (Matthew 7.15), Ysengrimus, a medieval epos presents the concept of wolf-monk as the image of a hypocritical and greedy monk, and also the Bestiaries are telling about unsympathetic character traits such as greed and extortion. Once wolves are dressed into cowls and are preaching for a ram for example, it is an obvious idea that Matthew 7.15 has played a crucial role in the development of the imagery. But also different kinds of more popular literature can be the source. The wolf is both the false prophet from the Bible as well as the hypocrite and deceiver in literature and the popular traditions. But fortunately the wolf will always be cheated at the end, and the ram, the sacrificial animal in the biblical sense, is the victorious. The article discusses whether the scene has a performative character, is a didactic allegory or symbolizes and visualizes the rite of baptism. Possible interpretations are made out from that conviction that no work of art in the medieval church is created without containing a certain form of communication to the congregation. Images can be highly variables in expressions and not always directly connected to the allegorical substance of the Bible, but generally speaking they have a relation to the power of the Almighty and to the way of salvation through God. Within this overriding theme, you can easily imagine that each image at the same time has contained several meanings and messages to the contemporaries. A modern observer will perceive the scene as a kind of performance, because also people of today are reacting with suspiciousness, when they see a disguised wolf.